An innovative time-domain simulation method for multirate RF circuit simulation - Oliveira, Jorge dos Santos Freitas de (2011)
This paper presents an innovative time-domain simulation method, especially conceived for simulating strongly nonlinear RF circuits whose state variables are all fluctuating in a fast-varying time scale, but evidence different time evolution rates in a slow envelope time scale. The method uses the mathematical method of lines based on modern multirate Runge-Kutta (MRK) schemes, and operates within a bivariate framework of an aperiodic slow time scale and a periodic fast time scale. This way, it can attribute different time-steps to slow and fast state variables in the envelope time evolution, considerably reducing the numerical simulation burden. Tests performed in an illustrative application example reveal, however, that its promising efficiency can be constrained by a stiffness restrictive scenario.